A Genome-Wide Approach to the Phylogeography of the Mussel Mytilus galloprovincialis in the Adriatic and the Black Seas - Paterno, Marta; Bat, Levent; Souissi, Jamila Ben; Boscari, Elisa; Chassanite, Aurore; Congiu, Leonardo; Guarnieri, Giuseppe; Kruschel, Claudia; Mačić, Vesna; Marino, Ilaria Anna Maria; Micu, Dragos; Milchakova, Nataliya; et al. (Frontiers in Marine Science, 2019)
Connectivity between populations shapes the genetic structure of species being crucial for an effective management of environmental resources. Genetic approaches can provide indirect measures of connectivity, allowing the identification of genetically differentiated - unconnected - populations. In this study, we applied a 2b-RAD approach based on hundreds of polymorphic loci to provide the first detailed insight into the population genomics of the Mediterranean mussel Mytilus galloprovincialis in part of its native geographical range. We sampled 19 localities within the Mediterranean and Black Seas, and analyzed a total of 478 samples. We detected strong differences between the two seas, whereas no differences were found between samples from the Western and Central Mediterranean and within Western Mediterranean samples. In the Central Mediterranean a significant differentiation emerged comparing Central Adriatic samples with those from South Adriatic and Ionian Seas. Furthermore, an East-to-West genetic structuring was found in the Central Adriatic Sea, which was not present in the Southern Adriatic and Ionian Seas. These results possibly reflect the local oceanography, with a Middle Adriatic gyre unable to prevent genetic differentiation in this species, and a Southern Adriatic gyre that effectively mixes propagules in Southern areas. In the Black Sea, no signal of genetic structure was found, although samples were spaced at similar distances as in the Adriatic-Ionian area. Genetic connectivity patterns of M. galloprovincialis reveal peculiar species-specific features respect to other species with similar larval duration, suggesting caution in using genetic connectivity data of single species in defining conservation units. We recommend of using genetic connectivity data of many species representing a variety of life history traits, and we call for new investigations using high resolution population genomics, particularly in the Black Sea, to understand if areas separated by hundreds of kilometers can be considered genetically connected as mussels’ data suggest. This information will be critical to ensure “a well-connected system of protected areas” according to Aichi Target 11 of the Convention on Biological Diversity.